Endoscopic Preoperative Assessment, Classification of Stenosis, Decision-Making - Filauro, Marta; Mazzola, Francesco; Missale, Francesco; Canevari, Frank Rikki; Peretti, Giorgio (Frontiers in Pediatrics, 2020)
Paediatric Laryngo-Tracheal Stenosis (LTS) comprises different conditions that require precise preoperative assessment and classification. According to the guidelines, the optimal diagnostic work-up of LTS patients relies both on a comprehensive anamnesis and on endoscopic and radiological assessments. All the causes of LTS result in an impairment in airflow, mucociliary clearance, phonation, and sometimes in swallowing disorders. The main goals of treatment are to maintain an adequate respiratory space and restore the Upper Aero-Digestive Tract (UADT) physiology. The first step when dealing with LTS patients is to properly assess their medical history. The main causes of paediatric LTS can be divided into two groups, i.e., congenital and acquired. The most common causes of congenital LTS are: laryngomalacia (60%), vocal fold paralysis (15-20%), subglottic stenosis (SGS) (10-15%), laryngeal webs and atresia (5%), subglottic haemangioma (1.5-3%), and others. On the other hand, 90% of acquired paediatric LTS cases are subsequent to post-intubation injuries. Other less frequent causes are: iatrogenic complications from endoscopic laryngeal interventions, benign tumours, caustic or thermal injuries, external blunt force injury or trauma, chronic inflammatory disorders or idiopathic causes. Diagnostic work-up consists in a step-by-step investigation: awake and asleep transnasal fiberoptic laryngoscopy (TNFL), direct laryngoscopy with 0° and angled telescopes to investigate the type of stenosis (arytenoid mobility, craniocaudal extension, involved anatomical sites, and active or mature scar tissue), and broncho-esophagoscopy to rule out associated mediastinal malformations. To date there are several available classifications for each of the involved sites: Cohen’s classification for anterior glottic stenosis, Bogdasarian’s for posterior glottic stenosis (PGS) and Myer-Cotton’s for subglottic stenosis, even though others are used in daily practice (Lano-Netterville, FLECS, etc.). The European Laryngological Society recently proposed a new classification which is applicable in all LTS cases. In this chapter we deal with preoperative assessment and staging, reviewing the most relevant classifications applicable in patients affected by LTS, conditio sine qua non in order to tailor the best treatment modality to each subject. We’ll also detail the comprehensive radiological, endoscopic and functional assessment for the correct use of each staging classification.